The Efficacy of Intravitreal Conbercept for Chronic Central Serous Chorioretinopathy - Jianbo Mao; Caiyun Zhang; Chenyi Liu; Lijun Shen; Jimeng Lao; Yirun Shao; Yiqi Chen; Jiwei Tao (Journal of Ophthalmology)
Purpose. To evaluate the efficacy and safety of conbercept for patients with chronic central serous chorioretinopathy (CSC). Methods. A retrospective clinical study. Thirty-one patients (35 eyes) with chronic CSC were given intravitreal injections of conbercept and followed up for at least 6 months. Observed indicators included best-corrected visual acuity (BCVA), central macular thickness (CMT), and resolution of subretinal fluid (SRF). Serial changes in BCVA and CMT were analyzed by using repeated measures analysis of variance. Results. During the 6-month follow-up, the mean number of injections required and performed was 1.77 ± 0.60. The logMAR BCVA was 0.48 ± 0.26 at the baseline, 0.34 ± 0.26, 0.30 ± 0.26, 0.27 ± 0.26, 0.24 ± 0.26, and 0.23 ± 0.26 at 2-week and 1-, 2-, 3-, and 6-month follow-ups, respectively (F = 27.173, P<0.05). CMT was 313.74 ± 144.51 μm at the baseline and decreased to 263.49 ± 120.44 μm, 225.91 ± 91.98 μm, 195.77 ± 66.69 μm, 189.74 ± 65.41 μm, and 199.49 ± 81.50 μm at 2-week and 1-, 2-, 3-, and 6-month follow-ups, respectively (F = 18.093, P<0.05). Full resolution of SRF was achieved in 8 (22.9%) eyes at 1 month, 16 (45.7%) eyes at 2 months, 22 (62.9%) eyes at 3 months, and 27 (77.1%) eyes at 6 months after the initial treatment of anti-VEGF injection. No severe adverse event was noted relevant to the therapy. Conclusions. Intravitreal injection of conbercept may effectively reduce the CMT and improve the BCVA in chronic CSC in a short term of 6 months.